PERAN KELUARGA DALAM PERKEMBANGAN MORAL ANAK : The Role of the Family in the Moral Development of Children - farihah, elyaum (Jurnal Al-Ilmu: Jurnal Penelitian dan Pendidikan Madrasah Ibtidaiyah, 2022)
This article is motivated by the important role of the family in the moral development of children. The family is the first educator for children, and the family is a very meaningful factor for children's learning, such as directing religious learning, and children's moral development. The purpose of this paper is to determine the role of the family in the moral development of children. This writing uses a literature study research method. The results of this paper indicate that the efforts made by parents in educating children are First, parents as role models for children, Second, parents as motivators for children, Third, parents as the main mirror of children, and Fourth, parents as facilitators of children. While the efforts of parents in the moral development of children include: First, introducing moral values ​​in society, Second, involving children in discussions about moral dilemmas, Third, instilling an attitude of love, Fourth, applying discipline to children, Fifth, generating feelings of guilt. in children, and the Sixth, giving examples.